High-Resolution Sampling of a Broad Marine Life Size Spectrum Reveals Differing Size- and Composition-Based Associations With Physical Oceanographic Structure - Greer, Adam T.; Lehrter, John C.; Binder, Benjamin M.; Nayak, Aditya R.; Barua, Ranjoy; Rice, Ana E.; Cohen, Jonathan H.; McFarland, Malcolm N.; Hagemeyer, Alexis; Stockley, Nicole D.; Boswell, Kevin M.; Shulman, Igor; et al. (Frontiers in Marine Science, 2020)
Observing multiple size classes of organisms, along with oceanographic properties, can improve our understanding of the drivers of aggregations, yet acquiring these observations remains a fundamental challenge in biological oceanography. By deploying multiple biological sampling systems, from conventional bottle and net samplers to new imaging and acoustic systems, we describe the coupling of different size classes of marine organisms (several microns to ~10 cm) to local and regional (m to km) physical oceanographic processes on the Delaware continental shelf. We also assessed trade-offs among imaging and acoustic systems. Although rarely evaluated (usually due to logistical constraints), examining abundances of organisms from multiple systems with some degree of size overlap of target taxa is critical for understanding data quality. Several high-resolution systems were deployed, including (in ascending order of target organism size) an imaging flow cytometer (CytoSense), a digital holographic imaging system (HOLOCAM), an In Situ Ichthyoplankton Imaging System (ISIIS), and multi-frequency acoustics (18 and 38 kHz). Although we expected to find aggregations near density interfaces, aggregations were sporadic, loosely tied to density structure for different size classes of particles, and likely would have been missed with traditional station-based sampling (~9-km resolution) with bottles and nets. Detected community composition was greatly dependent on size selectivity, camera resolution, and sampling method. Large zooplankton near the surface tended to be more abundant offshore and were primarily composed of appendicularians and gelatinous organisms. This region was also associated with higher organism abundances in the nets, ISIIS, and acoustics, but the nets showed a community dominated by copepods, while the ISIIS imaging showed preponderance of fragile, gelatinous organisms, and the HOLOCAM showed dense patches of ciliates. The high spatial coincidence of large particles (> 7.59 mm equivalent spherical diameter) in the ISIIS and acoustic backscatter suggests that gelatinous organisms were responsible for generating some portion of the scattering that tended to be more prevalent towards the shelf break. By systematically evaluating each system’s strengths and weaknesses, researchers can identify sampling techniques relevant to studying different ecological processes, aiding the design of efficient, hypothesis-driven sampling programs incorporating these relatively new technologies.